Propaganda speech in the Gulf press articles about the Qatari crisis An analytical study in the political articles published in the newspapers (Riyadh) Saudi Arabia and (Al-Ittihad) UAE from 5/6/2017 to 5/9/2017 - Ali Abud AL-Kadem, Amjed; Mahmoud Dulaimi, Nazhat (ALBAHITH ALALAMI, 2021)
Propaganda speech in the Gulf press articles about the Qatari crisis, an analytical study in the political articles published in the newspapers (Riyadh) Saudi Arabia and (Al-Ittihad) UAE from 5/6/2017 to 5/9/2017, University of Baghdad, College of Media, Press Department, 2019. The problem of the research was to monitor the contents of propaganda messages to Saudi Arabia and the UAE regarding the Qatari crisis, especially with the escalation of propaganda media campaigns between the four boycotting countries on the one hand and Qatar on the other hand, in light of crises and conflicts in the Gulf region and the Arab region in general. The researcher used the survey method to answer the research questions and achieve its results. This research is a descriptive research based on the method of analyzing the content in the collection of data and information related to the subject of the research. The researcher also used the method of discourse analysis (proof path) as a complementary measure to analyze the content